The Effect of Using Quizizz Paper Mode Learning Media on Student Learning Outcomes in Mathematics Subjects at SDN Setu 02 Jakarta - Muhammad Luthfi Apriadi; Zulfadewina Zulfadewina (Green Publisher Indonesia, 2024)
This study investigates the impact of using Quizizz Paper Mode as a learning medium on the mathematics learning outcomes of fifth-grade students at SDN Setu 02 Jakarta. Employing a quantitative research method with a Posttest-Only Control Design, the study involved two groups: an experimental group utilizing Quizizz Paper Mode and a control group relying on conventional teaching methods. The results demonstrate a significant improvement in the experimental group's post-test scores compared to the control group, indicating the effectiveness of Quizizz Paper Mode in enhancing students' mathematical understanding and engagement. The study's findings suggest that integrating technology like Quizizz Paper Mode in education can positively influence learning outcomes, though limitations such as sample size and focus on a single subject should be considered. The research underscores the need for further exploration and implementation of educational technologies in primary school curricula.